Edukasi dan Efektifitas Protokol Vetilasi, Durasi dan Jarak (VDJ) Pada Masa Pandemi Covid-19 di SMK Bali Kresna Medika - Kadek Primadewi (Jurnal Pengabdian UNDIKMA, 2022)
This community devotion aims to provide education on the ventilation protocol, duration and distance (VDJ) at the Bali Kresna Medika Vocational School to prevent infection of Covid-19. The method uses online-based education. Participants who took part in this activity were 58 students. The activity evaluation instrument uses a questionnaire and data analysis techniques using the N-Gain score. The result of this service activity is that there is an increase in the pretest score (before being given education) which is 60.86% to 87.18% in the posttest result (after being given education). Conclusions and suggestions there is a significant relationship with posttest scores, namely increasing after education, so that education on the effectiveness of the VDJ protocol (veilation, duration, distance) at the Bali Kresna Medika Vocational School during the new normal Covid-19 period.